2018
DOI: 10.17097/ataunizfd.403323
|View full text |Cite
|
Sign up to set email alerts
|

Erzurum Şartlarında Bazı Yem Bezelyesi Hat ve Çeşitlerinin Tohum Verimleri ile Bazı Özelliklerinin Belirlenmesi

Abstract: ürün yetiştirme sezonunda şansa bağlı tam bloklar deneme deseninde 3 tekrarlamalı olarak incelenmiştir. İki yıllık sonuçlara göre incelenen genotiplerin Erzurum şartlarındaki performanslarında önemli farklılıklar görülmüştür. 15 ve 10 numaralı hat ve Özkaynak çeşidi en yüksek tohum verimine sahip olmuşlardır. Bununla birlikte hasat indeksinde Taşkent, kışı geçirme oranında ise Özkaynak çeşidi ilk sırayı almıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The hay yields obtained from chicory during the grazing maturity period were found approximate or higher value than the hay yields were determined by Sanderson (2010) and Piluzza et al (2014) and reported by Tan and Temel (2012). This situation varied according to the soil, environment, type of variety used and the maintenance process applied.…”
Section: Hay Yieldmentioning
confidence: 65%
“…The hay yields obtained from chicory during the grazing maturity period were found approximate or higher value than the hay yields were determined by Sanderson (2010) and Piluzza et al (2014) and reported by Tan and Temel (2012). This situation varied according to the soil, environment, type of variety used and the maintenance process applied.…”
Section: Hay Yieldmentioning
confidence: 65%
“…The number of pods in peas was reported as 6.5 -9.9 number/plant (Önder andCeyhan 2001), 18.3 -38.3 number/plant (Ceyhan et al 2005), 12.3 -24.0 number /plant , 26.7-28.3 number /plant (Geren and Alan 2012), 10.4-15.5 number/plant (Tan et al 2012), 8.7-11. 4 number /plant (Uzun et al 2012), 8.2-9.2 number/plant (Kavut and Çelen 2017), 5.8-11.0 number/plant (Kadıoğlu andTan 2018), and14.6-17.3 number/plant (Keskin et al 2021) and the varieties had different pod numbers. While the results obtained in terms of the number of pods of the forage pea lines used in the experiment are in agreement with the results reported by , and Keskin et al (2021), higher than the results reported by Önder and Ceyhan (2001), Tan et al (2012), Uzun et al (2012), Kavut and Çelen (2017), Kadıoğlu and Tan (2018) but lower than the results reported by Geren and Alan (2012).…”
Section: Number Of Pods Per Plantmentioning
confidence: 99%
“…4 number /plant (Uzun et al 2012), 8.2-9.2 number/plant (Kavut and Çelen 2017), 5.8-11.0 number/plant (Kadıoğlu andTan 2018), and14.6-17.3 number/plant (Keskin et al 2021) and the varieties had different pod numbers. While the results obtained in terms of the number of pods of the forage pea lines used in the experiment are in agreement with the results reported by , and Keskin et al (2021), higher than the results reported by Önder and Ceyhan (2001), Tan et al (2012), Uzun et al (2012), Kavut and Çelen (2017), Kadıoğlu and Tan (2018) but lower than the results reported by Geren and Alan (2012). These differences are due to the genetic structure of these newly developed lines.…”
Section: Number Of Pods Per Plantmentioning
confidence: 99%
“…Agronomik uygulamalar içerisinde ekim normu ya da uygun ekim sıklığını sağlayan sıra aralıklarının bilinmesi yem bitkileri yetiştiriciliğinde yüksek miktar ve kalitede tohum verimlerinin alınabilmesi için büyük önem arz etmektedir. Ekim normları ise; bitkilerin genetik ve morfolojik yapıları, tohum canlılığı ve iriliği, üretim amaçları, ekim yöntemleri ve bölgenin ekolojik koşullarının (yağış miktarı ve dağılımı, sıcaklık, nem, toprağın fiziksel ve kimyasal özellikleri) yanı sıra kültürel uygulamalara (sulama, bitki sıklığı, gübreleme, tohum yatağının durumu) bağlı olarak değişkenlik gösterebilmektedir (Tan, 2018). Nitekim tohumluk üretimi amacıyla yetiştirilen farklı yem bitkisi ve alternatif türlerde yapılan (Martiniello ve Ciola, 1994;Bertero ve Ruiz, 2008;Geren ve ark., 2015;Kavut ve Çelen, 2017;Önkür ve Keskin, 2019;Soysal ve ark., 2020;Yılmaz, 2021), bazı araştırmacılar ise geniş sıra aralıları ile yetiştirilen bitkilerde tohum verimlerinin daha yüksek olduğunu ortaya koymuşlardır (Huebner, 2002;Bozoğlu ve ark., 2004;Türk ve Çelik, 2005).…”
Section: Introductionunclassified